Editorial: Fluorescent biosensors. Issue 2 (4th February 2014) - Morris, May C.; Blondel, Marc
<x xml:space="preserve">Abstract</x> This special issue of Biotechnology Journal on fluorescent biosensors is edited by Dr. May Morris and Prof. Marc Blondel. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>